Kepimpinan transformasi pensyarah dan kecerdasan emosi pelajar di universiti awam, Johor - Anbalagan, Mugambikai (2021)
This study devotes to examine the level of lecturers’ transformational leadership and students’ emotional intelligence of public universities in Johor, to identify the differences of Transformational Leadership among lecturers of public universities in Johor. To identify the relationship between the Transformational Leadership of Lecturers and Students’ Emotional Intelligence. This study used quantitative methods for data collections. Questionnaire distributed as research instruments to students of public universities in Johor. For quantitative data, use descriptive and inferential data to measure variable data. Questionnaires were distributed as research instruments to public university students namely University Technology Malaysia and University (UTM), Tun Hussein Onn (UTHM) in Johor. 300 questionnaire was distributed to public universities students, and 288 questionnaire was returned through google form due to Covid 19. Respondents selected from Johor public universities; IBM SPSS Statistic software version 23 will be used to collect data from the study This software can help researchers manage study data and perform statistics for the data obtained. Next, the study findings were analysed using non -parametric test result statistics. The results obtained found that the Level of Transformational Leadership of Lecturers and Emotional Intelligence of Students is high. Furthermore, the results of the Pearson Correlation Test showed no significant relationship between Lecturer Transformational Leadership and Students ’Emotional Intelligence.